Tarian Kebalai Kematian Sebagai Ruang Publik Solidaritas Sosial Masyarakat Rote Ndao - Yoggy Hermondi Manu; Tony Tampake (Indonesian Center for Religion and Society Studies (InTReSt), 2023)
The Kebalai death dance originates from the island of Rote Ndao. This dance is performed en masse regardless of social status and religion. The process is carried out by forming a circle, holding hands, then followed by a collective foot and hand movements following the rhythm of the poem. The Kebalai death dance aims to give the family left behind patience and fortitude so as not to drag on in prolonged grief. The purpose of this study is to determine the process of forming social solidarity that occurs in Rote society through the values of the Kebalai death dance. This research uses a descriptive qualitative method with an ethnographic research type. Data collection was carried out through interviews and observations conducted in Rote Ndao. This research found that the Kebalai death dance forms public spatial mechanical solidarity through the values of togetherness, equality, unity, and comfort represented in Kebalai death dance. This research concludes that the spatial formed in the Kebalai death dance is a shared spatial, joint footing, melting together, and collective morale of the entire Rote community to provide comfort to families who experience grief.